THE FACTORS OF SURABAYA CITY REGION ENCOURAGE IN RESERVATION THROUGH OFFLINE TRAVEL AGENT (TRAVEL AGENT BUREAU): CASE STUDY AT PT ANEKA KARTIKA TOURS AND TRAVEL SERVICES SURABAYA - Irra Chrisyanti Dewi; Heni Adhianata; Arnold Suwignyo (Journal of International Conference Proceedings (JICP), 2018)
This study want to know clearly about making a reservation through offline travel agent (Travel Agency)” and the study was conducted at PT. Aneka Kartika Tours and Travel Services Surabaya. Which is the mainstay of this research is the rise of online business travel agent in Indonesia that make entrepreneurs of offline travel agents or travel agency must be competed. This competition aims to make travel agency can remain superior to online travel agents. However, although online travel agent has been growing rapidly but still found the customers who come and requires the existence of a travel agency. Therefore the aim of this study was to determine: what are the factors that drive and influence the people of Surabaya to continue to use the service of offline travel agents. There are four main variables used in this study that are marketing mix, psychological factors, situational factors and social factors. The method used in researching is confirmatory factor analysis which it is a part of the SEM (Structural Equation Modeling). The population in this study are customers of PT. Aneka Kartika Tours and Travel Services Surabaya by distributing questionnaires to 120 customers, while the technique used is judgmental sampling. After distributing the questionnaire, the questionnaire results are calculated and processed using SPSS ver 21 and AMOS ver 21 thus it is produced a result that variable marketing mix, psychological factors, and situational factors are affected positively towards purchasing decisions through an offline reservation except on fourth variable that is social factors that should be eliminated because it has negative influence or do not contribute significantly. Keywords: offline travel agent, online travel agent, marketing mix, psychological factors, situational factors, social factors.